Run for life the complete guide for every female runner - Murphy, Sam 1968-; Jacob, Eddie (London Kyle Books, 2015)
Practical and engaging, this book will show you how to fit running into your everyday routine as well as encouraging you every step of the way. Suitable for all abilities - from the virtual runner who hasn't actually got round to getting their trainers on to the experienced runner lacking motivation and at risk of grinding to a standstill. Backed by scientific research, expert advice and the experiences of female runners, Sam shows you how to stay motivated, the best food and drink for maximum energy, the optimum stretches for top results and how to keep your programme balanced, realistic and challenging but, above all, fun.
First published in 2012 under the title Real Women Run.
Includes index.
Keywords: Running for women